Manajemen Pendidikan Agama Islam di Masjid berbasis Layanan Umat - Khaerul Anwar; Choeroni Choeroni; Mumtaz Fatimah az-Zahro (Universitas Islam Sultan Agung, 2022)
The rapid growth of mosques in Indonesia is a matter of pride for us Muslims. But it's really unfortunate, it turns out that the existence of hundreds of thousands of mosques in general are still only functioning as